Pengaruh Citra Toko dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan pada Toko Grosir Cirebon - Asep Gunawan (Universitas Peradaban, 2016)
The purpose of this study was to analyze the Store Image effect on customers loyalty, and Customer Satisfaction on customers loyalty and effect Store Image and Customer Satisfaction jointly towards Customer Loyalty in Grocery Stores Cirebon. The results showed that the image store did not significantly affect customer loyalty, while customer Satisfaction significant effect on the Customer Loyalty. Effect of Store Image and Customer Satisfaction jointly against significant effect of Customer Loyalty.